Questions that matter : - Miller, Ed. L. (McGraw-Hill, 2004)
This book offers an introduction to the major topics and fields of philosophy. While topically organized, presentations also reveal the historical development of philosophical ideas and figures. Primary source readings are woven into text discussions. New to the third edition are a philosophical dictionary, a timeline/map, and expanded coverage of Eastern philosophy and women. --This text refers to an out of print or unavailable edition of this title